Baseline Visual Acuity at Wet AMD Diagnosis Predicts Long-Term Vision Outcomes An Analysis of the IRIS Registry - Ho, Allen C (Ophthalmic surgery, lasers & imaging retina, 2020)
© 2020 Ho, Kleinman, Lum, et al.; licensee SLACK Incorporated.